Perlindungan Hukum Jaminan Kesehatan di Indonesia - Ezravania Rahmat; Gunardi Lie (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Social security is an important system in providing adequate protection and access to health services for the community. The most important social security is health insurance. Health insurance is regulated through specific laws and regulations. The implementation of Health Insurance involves the Health Insurance Administering Agency (BPJS) as the one that manages the health insurance program. BPJS is responsible for managing funds, paying claims, setting service rates, monitoring service quality and providing information and education to participants. With the collaboration between BPJS Health and health facilities (Hospitals) through cooperation agreements to ensure access and quality of health services in accordance with established standards. In its implementation related to law enforcement, the effectiveness of the law, public awareness and compliance must be evaluated through several variables of target accuracy, program socialization, achievement of program objectives and implementation monitoring that affect health insurance. The research method used is normative legal research which is descriptive analytical in nature which describes precisely the characteristics of an individual, situation, symptom or particular group and to determine whether or not there is a relationship between a symptom and other symptoms in society. The type of data used is from literature, official documents. The data collection technique used was a literature study with additional interviews from the Health Social Security Administration (BPJS) and one at the hospital. With this health insurance program, some people have registered, but for those who have not registered, BPJS should provide outreach to its participants. In the event that the complaint process is carried out in less days than specified in the regulations.